THE DETERMINATION OF THE RESISTANCE MOVEMENT COMPACTORS SOIL ON A FLAT SURFACE - Hlavatskyi, K. Ts.; Cherkudinov, V. Ye. (Science and Transport Progress, 2008)
Variants of reducing the resistance to moving of a vibrorammer on flat surface are presented.